Effect of liquid-liquid transition on solidification and wettability of Sn-0.7Cu-xBi solder - Li, X. F. (2021)
The electrical resistivity-temperature curve (ρ-T) of Sn-0.7Cu-xBi (wt.%) melts was measured, and anomalous changes were observed on the ρ-T curve at the temperature far above the corresponding liquidus. The results reveal that the melts have experienced a temperature-induced liquid-liquid transition (LLT), and the transition is reversible after the first cycle heating. Based on the result of LLT, solidification experiments and spreadability testing were carried out on the Sn-0.7Cu-xBi alloy to investigate the effect of LLT on the solidification and wettability. The results show that the microstructure was refined, and the wettability was improved when the solder samples solidified from the melt experienced LLT.